DAKWAH DI MEDIA SOSIAL DARING: TINJAUAN CERAMAH KHALID BASALAMAH DI YOUTUBE - Suharto Suharto; Nurunnisa Mutmainna (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2019)
This study examines the strategies and content of da`wah Basalamah’s in online video sharing media, Youtube. The video content reviewed is the video uploaded on the official Khalid Basalamah Official account in July 2017. Based on the analysis with the content analysis approach, this article shows that Khalid Basalamah is very active in disseminating his da`wah content via Youtube by uploading, at least, one video content in one day. The contents of Basalamah’s lectures uploaded in July 2017 put forward the themes of theology, apocalypse, morals, repentance, loyalty, patience, and apologize to others. No content touches the subject of sharia and dealings (mu’āmalah). Studies of preaching on Youtube media need to be developed, considering that preaching through the media is very popular among dai in Indonesia nowadays.